Leading Schools for Innovation and Change: A Case Study of Successful Schools - Shiwakoti, Krishna Prasad (Journal of TESON, 2022)
This study explores the role and leadership management practices of head teachers in public schools. In schools, the leadership goals are for developing innovative and excellent student outcomes. The data were collected from interviews with five head teachers or principals of five schools. The findings showed that the innovative head teachers adopted several leadership strategies to enhance the school's success and quality enhancement. An innovative model for innovative leadership was developed that provided a road map of the influence for their leadership. This study makes clear that head teachers have experienced noticeable success in school’s quality enhancement through establishing innovative cultures. The findings of this study imply that leadership behavioral changes can lead to great positive impacts in improving school’s teaching and learning quality.